The power of credibility: How influencer credibility impacts impulsive buying in live-streaming commerce - Setyanta, Budi; Suryaningtiyas, Yosita Dwiani; Arum, Maliana Puspa; Fauzi, Rizal Ula Ananta; Kadi, Dian Citaningtyas Ari (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
Live-streaming commerce has grown increasingly popular in the last few years. It allows influencers to show and explain products in real-time while viewers can make purchases instantly. This study decisively examines the impact of people’s trust in influencers on their propensity to make impulse purchases. The researchers collected the information through an online questionnaire from 297 participants, who were selected using convenience sampling based on their availability and ease of access. The responses were then analyzed using the PLS-SEM method. The findings indicate that trust in influencers significantly influences consumers’ emotional reactions and impulsive purchasing decisions. Those who have doubts are reluctant to make purchases; those who think the influencer is trustworthy make rapid purchase decisions. A barrier, uncertainty leaves consumers to consider their options. This outcome underlines the need of companies and influencers to lower uncertainty during live-streaming events. They can fulfill this by providing honest, open information, proving the quality of the good, and quickly answering questions. By doing this, one promotes confidence and faster purchase decisions. According to this study, influencing impulse buying mostly depends on trust and clarity. Hence, organizations could boost their live-stream marketing campaigns and increase sales by utilizing these elements.